2017
DOI: 10.1364/oe.25.016761
|View full text |Cite
|
Sign up to set email alerts
|

Compact photoacoustic module for methane detection incorporating interband cascade light emitting device

Abstract: A photoacoustic module (PAM) for methane detection was developed by combining a novel 3.2 μm interband cascade light emitting device (ICLED) with a compact differential photoacoustic cell. The ICLED with a 22-stage interband cascade active core emitted a collimated power of ~700 μW. A concave Al-coat reflector was positioned adjacent to the photoacoustic cell to enhance the gas absorption length. Assembly of the ICLED and reflector with the photoacoustic cell resulted in a robust and portable PAM without any m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…For some applications that do not need high power, a broadband incoherent mid-IR source with continuous, rather than abrupt, L-I response (i.e., no threshold) is preferred. These include certain spectroscopic techniques for chemical detection [169][170][171], particularly multi-point sensors that require low unit cost, and dynamic IR scene projection [172]. Although mid-IR LEDs have been investigated for several decades [173,174], the maximum continuous wave output powers for packaged commercial devices operating at room temperature are still ≤ 300 µW.…”
Section: Interband Cascade Ledsmentioning
confidence: 99%
“…For some applications that do not need high power, a broadband incoherent mid-IR source with continuous, rather than abrupt, L-I response (i.e., no threshold) is preferred. These include certain spectroscopic techniques for chemical detection [169][170][171], particularly multi-point sensors that require low unit cost, and dynamic IR scene projection [172]. Although mid-IR LEDs have been investigated for several decades [173,174], the maximum continuous wave output powers for packaged commercial devices operating at room temperature are still ≤ 300 µW.…”
Section: Interband Cascade Ledsmentioning
confidence: 99%
“…In order to improve the detection sensitivity and achieve the flow measurement, a variety of resonant PA cells with buffers were used. Zheng et al used a 22-stage mid-infrared interband cascade light emitting device (ICLED) with an optical power of ~700 μW to emit excitation light into a differential resonant PA cell to detect CH4 [21]. When the integral time was 1 s, the assembled system showed that the MDL was ~3.6 ppm.…”
Section: Design Of the Pa Microcavity Sensormentioning
confidence: 99%
“…The differential photoacoustic cell was designed as shown in Fig. 3a, which resembles the well-known differential Helmholtz resonator (Starecki and Geras, 2014;Zeninari et al, 1999;Zheng et al, 2017). It has two identical 90 mm parallel tube-shaped channels with diameters of 8 mm as two acoustic resonators.…”
Section: Design Of the Cavity-enhanced Photoacoustic Modulementioning
confidence: 99%